Emission taxation, green innovations and inverted-U aggregate R&D efforts in a linear state oligopoly game - Davide Dragone; Luca Lambertini; Arsen Palestini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
We revisit the well known differential Cournot game with polluting emissions dating back to Benchekroun and Long (1998), proposing a version of the model in which environmental taxation is levied on emissions rather than the environmental damage. This allows to attain strong time consistency under open-loop information, and yields two main results which can be summarized as follows: (i) to attain a fully green technology in steady state, the regulator may equivalently adopt an appropriate tax rate (for any given number of firms) or regulate market access (for any given tax rate); (ii) if the environmental damage depends on emissions only (i.e., not on industry output) then the aggregate green R&D effort takes an inverted-U shape, in accordance with Aghion et al. (2005), and the industry structure maximising aggregate green innovation also minimises individual and aggregate emissions.
Keywords: C73; H23; L13; O31; Q52; 330; pollution; green R&D; emission taxation; differential games